Analysis of plant phenology dynamics in Spain from 1983 to 2020 using satellite imagery - Adell Michavila, Maria; Vicente-Serrano, Sergio M.; Montorio Llovería, Raquel; Cai, ZangZang; Eklundh, Lars (Cuadernos de Investigación Geográfica, 2024)
This study spatially analyzes plant phenology and its variations over time in mainland Spain and the Balearic Islands. To conduct the analysis, a nearly 40-year span time series (1983-2020) was generated by merging NDVI vegetation index values from satellite images sourced from NOAA-AVHRR and MODIS sensors. The phenological variables were calculated using TIMESAT 3.3, which extracted 13 phenometrics whose trends were evaluated using the Theil-Sen model, and their significance was assessed with the Mann-Kendall test. The results reveal regional differences between Eurosiberian Spain and the Mediterranean region regarding the start and end phases of the season. On average, the Eurosiberian zones have experienced delays in their season start and end dates, by approximately 0.35 and 0.22 days per year over the study period, respectively, while the Mediterranean region has seen an advancement in leaf-out and senescence dates by about 0.07 and 0.05 days per year. A greening trend across the entire study area and significant contrasts among land covers have also been observed, opening avenues for future studies to delve deeper into these behavioral differences and their interactions with changes in climate and land management.